Improving Efficiency of the Process and Safety by Low-Cost Automation - Srinivasan, V.; Veeranaath, V.; Santhakumar, J. (International Journal of Psychosocial Rehabilitation, 2019)
In the growing competition in market because of globalization, it’s imperative that the product should be reach customer on time delivery. All the organization will follow to manufacture products with the standards and procedures like SAFETY, QUALITY, COST and TIME. By following the safety in our mind, we should get the quality product in time. A quality product will reduce the cost of the company. If all the chains are followed the product will be on time delivery. Therefore to increase the efficiency of the press line of 5400T (xl) and to achieve zero accidents in the sheet metal pressing and handling area it’s required to minimize the manual handling with less cost. In RNAIPL currently most of operation they are using manpower to collect the inner car body panels (pressed sheet). All the panels are having sharp edges. So the processing time is being increased because safety issues. The aim of the project is to eliminate the manpower, to improve on safety and to achieve the Design Standard Time Ratio (DSTR) which reduces the usage external sources (Air, Electric power, Hydraulic) with low cost automation.